Lithium ion battery silicon-carbon negative electrode aqueous binder and preparation method and application thereof

By using a water-based binder prepared in combination of carboxymethyl cellulose, solution polymer and emulsion polymer in the silicon carbon anode of lithium-ion batteries, the problems of poor stability and insufficient environmental protection in the prior art are solved, and a high-performance and environmentally friendly battery anode material is realized.

CN119890310APending Publication Date: 2025-04-25GUOKE GUANGHUA SHAOGUAN NEW MATERIALS RES INST +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411643928.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery silicon-based negative electrode water-based adhesives have problems such as poor stability, affected ionic conductivity and insufficient environmental protection during the preparation process, and it is difficult to have excellent strength and toughness, ideal electrochemical performance and economical and environmental protection.

Method used

Using a combination of carboxymethylcellulose, solution polymer and emulsion polymer, aqueous binders are prepared through solution polymerization and emulsion polymerization, and their proportions and group designs are adjusted to adjust the performance of the binder.

Benefits of technology

It realizes excellent mechanical properties and stability of silicon carbon anode of lithium-ion batteries, improves the cycling performance and capacity retention rate of the battery, and reduces environmental pollution and meets green and environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890310A_ABST
    Figure CN119890310A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials and adhesives, and discloses a lithium ion battery silicon-carbon negative electrode water-based adhesive as well as a preparation method and application thereof. The binder comprises a first component carboxymethyl cellulose, a second component solution copolymer and a third component emulsion copolymer, and according to the solid content, the mass ratio of the first component to the sum of the second component and the third component is 1: 0.5-1: 5. The binder is endowed with excellent mechanical properties, stability, electrolyte affinity and energy efficiency by adjusting the proportion of all the components and designing functional groups. A water-based polymerization system is adopted, so that the compatibility of the components and the stability of the slurry are ensured. In addition, the binder does not contain toxic organic solvents and meets the environmental protection requirement, the preparation method is simple and convenient, raw materials are easy to obtain, and the binder has the remarkable economical advantage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of battery materials and adhesives, and in particular to a lithium-ion battery silicon-carbon negative electrode aqueous binder and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, aerospace, military and large energy storage equipment due to their high energy density, high operating voltage, long cycle life, no memory effect, low self-discharge rate and environmental protection characteristics. With the development of lithium-ion batteries, the requirements for their capacity, high and low temperature resistance and cycle life are constantly increasing, and battery slurry plays a vital role in the battery manufacturing process. The stability of the slurry directly affects the coating quality, which in turn affects the cycle life of the battery. Graphite, as a traditional negative electrode material, is currently the preferred material due to its high capacity retention, low volume change, low cost and low toxicity. However, its maximum specific capacity (372mAh / g) limits the energy density of lithium-ion batteries. Silicon-based materials are considered to be the most promising high-energy density anode materials due to their high theoretical capacity (which can reach 4200mAh / g). However, the silicon-based anode has a large volume change during the charge and discharge process, resulting in electrode pulverization and instability of the solid electrolyte interface (SEI), low coulombic efficiency, and affecting its commercial application.

[0003] Binders are important auxiliary materials in lithium-ion batteries and have an important influence on the mechanical properties and electrochemical properties of electrodes. Non-aqueous binders such as PVDF require the use of toxic organic solvents during the preparation process, which is not conducive to environmental protection, and have poor adhesion to electrode active materials, making it difficult to suppress the volume change of materials during charging and discharging, resulting in poor battery cycle stability. Aqueous binders such as acrylic copolymers, sodium alginate and carboxymethyl cellulose, etc., because they contain a large number of polar functional groups, have strong intermolecular forces with active substances, have good adhesion, and do not require the use of toxic solvents during the preparation process, which improves environmental protection, but the hardness of aqueous binders is relatively high, and the electrode sheets prepared therefrom are prone to cracking and powdering on the surface when the volume of the active material changes. CN111430712A discloses a method for preparing a novel silicon-based negative electrode battery binder, which is prepared by heat-induced cross-linking polymerization of acrylic acid monomers and the like to form a cross-linked PAA binder. However, polar binders such as acrylic polymers have the defects of high binder hardness and insufficient flexibility due to their high crystallinity. Therefore, in silicon-based negative electrode slurry, styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are often used as a composite binder to adjust its performance. CN201610041306.0 discloses a silicon-based negative electrode composite binder containing CMC and SBR, which can solve the problem of low battery life caused by severe volume expansion of silicon-based materials. However, the components of such binders are simply physically mixed, and SBR is easy to float and CMC is difficult to dissolve during the pulping process, which leads to the problems of poor slurry stability and affected ion conductivity, which is not conducive to the preparation of high-quality negative electrode sheets. CN115832308 A discloses a double network water-based binder, which includes a high proportion of water-based polymers (85-99.4wt%) and a small amount of CMC (<10wt%) and a cross-linking agent (<5wt%), which is beneficial to slurry stability and improves the capacity retention rate of silicon-carbon negative electrodes. However, the water-based polymers are all prepared using water-soluble monomers with polar groups, which limits the adjustability of the binder in terms of toughness. In addition, an excessively high proportion of water-soluble polymers will significantly increase the cost of raw materials and processes, and the cross-linking agents therein also have certain environmental and safety issues.

[0004] Therefore, developing a highly compatible silicon-based negative electrode aqueous binder that has excellent strength and toughness, ideal electrochemical properties, and is economical and environmentally friendly is an urgent problem to be solved in this field. Summary of the invention

[0005] In view of the problems existing in the prior art, the primary purpose of the present invention is to provide an aqueous binder for silicon-carbon negative electrodes of lithium-ion batteries.

[0006] Another object of the present invention is to provide a method for preparing an aqueous binder for a lithium-ion battery silicon-carbon negative electrode.

[0007] Another object of the present invention is to provide an application of the above-mentioned lithium-ion battery silicon-carbon negative electrode aqueous binder.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A lithium ion battery silicon-carbon negative electrode aqueous binder, comprising a first component of carboxymethyl cellulose, a second component of a solution polymer and a third component of an emulsion polymer;

[0010] Calculated by solid content, the mass ratio of the first component to the sum of the second component and the third component is 1:0.5 to 1:5.

[0011] Furthermore, based on solid content, the mass ratio of the first component to the sum of the second component and the third component is 1:0.5 to 1:4; the mass ratio of the second component to the third component is 1:1 to 1:4, more preferably 1:1 to 1:2;

[0012] The solution polymer is obtained from polar monomers through solution polymerization, and the emulsion polymer is obtained from polar monomers and non-polar monomers through emulsion polymerization.

[0013] Furthermore, the molecular weight M of the carboxymethyl cellulose is W The molecular weight of the carbonyl group is 90,000 to 700,000, and the degree of substitution is 0.7 to 1.2.

[0014] Furthermore, the second component is prepared by the following steps: premixing the polar monomer acrylic acid with at least one of β-acryloxypropionic acid, vinyl acetate, acrylonitrile and acrylamide to obtain a premixed monomer, adding a neutralizer and then adding water to obtain a reaction solution, adding an initiator and heating in a deoxygenated environment to perform a solution polymerization reaction to obtain the second component.

[0015] Furthermore, the mass proportion of acrylic acid in the premixed monomer is 40-80%;

[0016] The mass concentration of the monomer in the reaction solution is 20-30%;

[0017] The adding of the neutralizing agent is to neutralize 20-60% of the total carboxylic acid in the premixed monomers, and the neutralizing agent is lithium hydroxide or ammonia water.

[0018] Furthermore, the solution polymerization reaction is carried out at a temperature of 65 to 85° C. and for a time of 2 to 3 hours.

[0019] Furthermore, the solid content of the solution polymer is 5-30%.

[0020] Furthermore, the third component is prepared by the following steps: premixing a polar monomer and a non-polar monomer to obtain a premixed monomer, adding an emulsifier and an appropriate amount of water to emulsify to obtain a pre-emulsion, adding an initiator to a portion of the pre-emulsion to obtain a seed pre-emulsion, heating and performing seed emulsion polymerization in a deoxygenated environment, then dripping the remaining pre-emulsion and heating again to perform a subsequent emulsion polymerization reaction to obtain the third component;

[0021] The polar monomer is at least one of methacrylic acid, acrylic acid, acrylonitrile, acrylamide, β-acryloxypropionic acid and vinyl acetate;

[0022] The non-polar monomers are at least two of methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate and styrene.

[0023] Further, the non-polar monomer accounts for 80-95% of the total mass of the premixed monomers;

[0024] The emulsifier is one or more of sodium dodecylbenzene sulfonate (SDBS), nonylphenol polyoxyethylene ether-10 (OP-10), reactive emulsifier SR-10 and reactive emulsifier DNS-86, and the added amount is 4-8% of the total mass of the premixed monomers.

[0025] Furthermore, the amount of pre-emulsion used in the seed emulsion polymerization is 40-50wt%, the temperature is 65-75°C, and the time is 10-30min.

[0026] Furthermore, the remaining pre-emulsion is added dropwise for 1 to 2 hours at a temperature of 70 to 85° C. for 2 to 3 hours.

[0027] Furthermore, the solid content of the emulsion polymer is 5-40%.

[0028] Furthermore, the initiator is ammonium persulfate or potassium persulfate, and the added amount is 0.5-1% of the total mass of the premixed monomers.

[0029] The preparation method of the above-mentioned lithium ion battery silicon-carbon negative electrode aqueous binder comprises the following steps:

[0030] The first component, the second component and the third component are mixed in a certain mass ratio, the pH value is adjusted to 5-9, and the mixture is stirred to obtain a lithium ion battery silicon-carbon negative electrode aqueous binder.

[0031] Furthermore, the stirring is performed at 200-500 rpm for 8-12 hours.

[0032] The application of the above aqueous binder in the negative electrode of silicon-carbon lithium-ion battery.

[0033] Furthermore, the battery negative electrode comprises a negative electrode substrate (copper foil) and a negative electrode material coated on the substrate, and the negative electrode material comprises an active material, a conductive aid and the above-mentioned aqueous binder.

[0034] Furthermore, the aqueous binder is added in an amount of 5 to 15 wt %.

[0035] The battery negative electrode is prepared by the following steps: active materials, conductive additives and aqueous binders are mixed in a dispersant according to a mass ratio to obtain a uniform slurry, and then the slurry is applied on a negative electrode substrate copper foil, and a 100-150 μm scraper is used to apply it into a flat and smooth film, and vacuum drying is performed at 100-150° C. for 6-10 hours, and cutting is performed to obtain a battery negative electrode sheet.

[0036] Furthermore, the active material is a silicon-based alloy, wherein the silicon content is 10-20%.

[0037] Furthermore, the conductive additive is one or more of carbon nanotubes, graphene, SuperP or Ketjen black.

[0038] Furthermore, the dispersant is pure water or ethanol aqueous solution, wherein the volume fraction of ethanol is 20-50%.

[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] (1) The aqueous binder of the present invention is based on a combination of carboxymethyl cellulose (first component) and polyacrylate solution polymer (second component) and emulsion polymer (third component). The various properties of the binder can be flexibly adjusted through proportion and group design to make it have excellent mechanical properties and stability suitable for silicon carbon negative groups. The polar groups therein achieve good bonding force and electrolyte affinity, which is beneficial to improving the cycle performance and capacity retention rate of the battery.

[0041] (2) The present invention adopts a water-based dispersion polymerization system and a water-soluble carboxymethyl cellulose, which not only ensures good compatibility and stability between the components of the binder, but also further facilitates the stability of the slurry. The synergistic effect of polar monomers and non-polar monomers achieves a balance between flexibility and rigidity and improves the anti-structural expansion and ionic conductivity of the binder.

[0042] (3) The binder does not contain toxic organic solvents and adopts a water-based system. While maintaining good processing performance and electrochemical performance, it significantly reduces environmental pollution and meets green environmental protection requirements. In addition, the raw material source is wide and the preparation method is simple, which has a good economic advantage. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1It is the Fourier infrared spectrum of the water-based binder prepared in Example 4 of the present invention.

[0044] Figure 2 It is the Fourier infrared spectrum of the water-based binder prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The present invention will be described in more detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. According to the embodiments of the present invention, all other embodiments obtained by technicians in the relevant fields without creative work are within the protection scope of the present invention, and for process parameters not specifically noted, conventional techniques can be used.

[0046] Embodiment 1:

[0047] Select M W The first component is prepared by premixing 80% acrylic acid and 20% acrylonitrile monomers, adding lithium hydroxide to neutralize 20% of the total carboxylic acid, adding 0.5% ammonium persulfate and diluting with water to a monomer mass concentration of 30% to obtain a reaction solution, heating the reaction solution to 75°C and polymerizing it under nitrogen protection for 2 hours to obtain a transparent aqueous solution copolymer with a certain viscosity. After the polymerization is completed, cool it to room temperature, add lithium hydroxide to adjust the pH to 6. Preparation of the third component: Premix 10% acrylic acid, 70% butyl acrylate and 20% propylene isooctyl ester monomers, add 5% of the total mass of the mixed monomers, and dilute with water to a mixed monomer mass concentration of 40%, and emulsify at 1500rpm for 30 minutes to obtain a pre-emulsion. Take 40% of the pre-emulsion, add 0.5% of the initiator ammonium persulfate to the total mass of the mixed monomer under nitrogen protection to obtain a seed pre-emulsion. Heat the seed pre-emulsion to 70°C for 15 minutes, then heat to 80°C, dropwise add the remaining pre-emulsion within 2 hours and keep warm for 1 hour to obtain a stable translucent polymer aqueous emulsion. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 6.

[0048] Preparation of aqueous binder: The first component, the second component and the third component were mixed at a mass ratio (calculated according to solid content) of 4:1:1, the pH was adjusted to 6 and the solid content was 20%, and stirred at 200 rpm for 10 hours.

[0049] Preparation of silicon-carbon negative electrode: The active material SiC (silicon content 13%), the conductive additive SuperP and the aqueous binder are dispersed in water at a ratio of 7:2:1 to obtain a slurry. The slurry is then applied to a copper foil and scraped into a flat and smooth film using a 100 μm scraper, and dried in a vacuum oven at 120 ° C for 8 hours, and then cut into silicon-carbon negative electrode sheets suitable for assembling batteries.

[0050] Embodiment 2:

[0051] Select M W The first component is 90000 and the degree of substitution is 0.7 carboxymethyl cellulose, which is dissolved in water and has a solid content of 2%. Preparation of the second component: pre-mix the monomers of 60% acrylic acid, 30% acrylonitrile and 10% β-acryloxy propionic acid by mass percentage, add lithium hydroxide to neutralize 40% of the total carboxylic acid, add 0.5% ammonium persulfate by mass concentration and dilute with water to a monomer mass concentration of 30% to obtain a reaction solution, heat the reaction solution to 75°C and polymerize under nitrogen protection for 3 hours to obtain a transparent aqueous solution copolymer with a certain viscosity. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 7. Preparation of the third component: pre-mix the monomers of 10% acrylic acid, 60% butyl acrylate and 30% methyl methacrylate by mass percentage, add 3% of the total mass of the mixed monomers, and dilute with water to a mixed monomer mass concentration of 35%, and emulsify at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 40% of the pre-emulsion, add 0.6% of the total mass of the mixed monomer as initiator ammonium persulfate under nitrogen protection to obtain a seed pre-emulsion. Heat the seed pre-emulsion to 75°C for 20 minutes, then heat to 85°C, dropwise add the remaining pre-emulsion within 1.5 hours and keep warm for 1 hour to obtain a stable translucent polymer aqueous emulsion. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 7.

[0052] Preparation of aqueous binder: The first component, the second component and the third component were mixed in a mass ratio of 1:2:2, the pH was adjusted to 7 and the solid content was 20%, and stirred at 200 rpm for 10 hours.

[0053] Preparation of silicon-carbon negative electrode: The active material SiC (silicon content 13%), the conductive additive SuperP and the aqueous binder are dispersed in ethanol with a volume concentration of 20% in a ratio of 7:2:1 to obtain a slurry. The slurry is then applied to a copper foil and scraped into a flat and smooth film using a 100μm scraper, and dried in a vacuum oven at 120°C for 8 hours, and then cut into silicon-carbon negative electrode sheets suitable for assembling batteries.

[0054] Embodiment 3:

[0055] Select M WThe first component is a carboxymethyl cellulose with a weight percentage of 250,000 and a degree of substitution of 0.7, which is dissolved in water and has a solid content of 1%. Preparation of the second component: pre-mix the monomers of 60% acrylic acid, 20% acrylonitrile and 20% vinyl acetate, add lithium hydroxide to neutralize 40% of the total carboxylic acid, add 0.6% ammonium persulfate and dilute with water to a monomer mass concentration of 30% to obtain a reaction solution, heat the reaction solution to 75°C and polymerize under nitrogen protection for 3 hours to obtain a transparent aqueous solution copolymer with a certain viscosity. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 7. Preparation of the third component: pre-mix the monomers of 10% acrylic acid, 60% butyl acrylate and 30% styrene, add 4% of the total mass of the mixed monomer emulsifier OP-10+SDBS (mass ratio 1:1) and dilute with water to a mixed monomer mass concentration of 35%, and emulsify at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 50% of the pre-emulsion, add 0.6% of the total mass of the mixed monomer as initiator ammonium persulfate under nitrogen protection to obtain a seed pre-emulsion. Heat the seed pre-emulsion to 75°C for 15 minutes, then heat to 85°C, dropwise add the remaining pre-emulsion within 1.5 hours and keep warm for 1 hour to obtain a stable translucent polymer aqueous emulsion. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 7.

[0056] Preparation of aqueous binder: The first component, the second component and the third component were mixed at a mass ratio of 2:1:1, the pH was adjusted to 7 and the solid content was 15%, and stirred at 300 rpm for 8 hours.

[0057] Preparation of silicon-carbon negative electrode: The active material SiC (silicon content 13%), the conductive additive SuperP and the aqueous binder are dispersed in ethanol with a volume concentration of 20% in a ratio of 7:2:1 to obtain a slurry. The slurry is then applied to a copper foil and scraped into a flat and smooth film using a 100μm scraper, and dried in a vacuum oven at 120°C for 8 hours, and then cut into silicon-carbon negative electrode sheets suitable for assembling batteries.

[0058] Embodiment 4:

[0059] Select M WThe first component is prepared by premixing 40% acrylic acid, 40% acrylonitrile and 20% acrylamide monomers, adding lithium hydroxide to neutralize 40% of the total carboxylic acid, adding 0.6% ammonium persulfate and diluting with water to a monomer mass concentration of 30% to obtain a reaction solution, heating the reaction solution to 75°C and polymerizing under nitrogen protection for 3 hours to obtain a transparent aqueous solution copolymer with a certain viscosity. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 7. Preparation of the third component: Premix 10% acrylic acid, 10% methacrylic acid, 70% butyl acrylate and 10% methyl methacrylate monomers, add 4% of the total mass of the mixed monomer emulsifier OP-10+SDBS (mass ratio 1:1) and dilute with water to a mixed monomer mass concentration of 35%, and emulsify at 2000rpm for 30 minutes to obtain a pre-emulsion. Take 50% of the pre-emulsion, add 0.6% of the total mass of the mixed monomer as initiator ammonium persulfate under nitrogen protection to obtain a seed pre-emulsion. Heat the seed pre-emulsion to 75°C for 20 minutes, then heat to 85°C, dropwise add the remaining pre-emulsion within 2 hours and keep warm for 1 hour to obtain a stable translucent polymer aqueous emulsion. After the polymerization is completed, cool to room temperature and add lithium hydroxide to adjust the pH to 8.

[0060] Preparation of aqueous binder: The first component, the second component and the third component were mixed at a mass ratio of 2:1:1, the pH was adjusted to 7 and the solid content was 15%, and stirred at 300 rpm for 8 hours.

[0061] Preparation of silicon-carbon negative electrode: The active material SiC (silicon content 13%), the conductive additive SuperP and the aqueous binder are dispersed in ethanol with a volume concentration of 20% in a ratio of 7:2:1 to obtain a slurry. The slurry is then applied to a copper foil and scraped into a flat and smooth film using a 100μm scraper, and dried in a vacuum oven at 120°C for 8 hours, and then cut into silicon-carbon negative electrode sheets suitable for assembling batteries.

[0062] Figure 1 Fourier infrared spectrum of the water-based binder prepared in Example 4, compared with pure CMC ( Figure 2 ) 1750cm -1 The characteristic peak signal generated by nearby C=O is enhanced, 3200cm -1 The nearby -OH signal weakened, indicating that the second and third components and CMC were partially esterified at high temperature, resulting in in-situ cross-linking, forming a three-dimensional multi-cross-linked network of hydrogen bonds and chemical bonds.

[0063] Comparative Example 1:

[0064] Select carboxymethyl cellulose with a MW of 250,000 and a degree of substitution of 1.2, dissolved in water as an aqueous binder with a solid content of 1%. Preparation of silicon-carbon negative electrode: The active material SiC (silicon content 13%), the conductive aid SuperP and the aqueous binder are dispersed in ethanol with a volume concentration of 20% in a ratio of 7:2:1 to obtain a slurry. The slurry is then applied to a copper foil and scraped into a flat and smooth film using a 100 μm scraper, and dried in a vacuum oven at 120 ° C for 8 hours, and then cut into silicon-carbon negative electrode sheets suitable for assembling batteries. Figure 2 The Fourier infrared spectrum of the aqueous binder prepared in Comparative Example 1 is shown in Table 1. Figure 1 In addition to the signal differences of C=O and -OH, the 2800-3000cm - 1 area alkyl peak intensity is low and smooth, while the spectrum of Example 4 ( Figure 1 ) The CH stretching vibration is relatively strong here, which proves the successful introduction of functional groups such as butyl acrylate.

[0065] Comparative Example 2:

[0066] Different from Example 4, no second component was added.

[0067] Comparative Example 3:

[0068] Different from Example 4, no third component was added.

[0069] Adhesive performance test:

[0070] The binder and negative electrode obtained in Examples 1-4 and Comparative Example 1 were assembled with a metal lithium electrode, a separator and an electrolyte to form a half-cell. Among them, the separator selected a commercial PP separator (25 μm), the electrolyte selected a 1 mol / L lithium hexafluorophosphate, and the solvent was ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (1v:1v:1v). The initial coulomb efficiency, the average discharge specific capacity within 200 cycles, and the capacity retention rate after 200 cycles were recorded by a 1C constant current charge and discharge cycle test, and the test results are summarized in Table 1.

[0071] Table 1 Adhesive performance test results

[0072]

[0073] It can be clearly seen from Table 1 that Examples 1 to 4 of the present invention have significantly improved electrochemical performance compared with Comparative Example 1. Among them, Example 2 has better specific capacity and capacity retention rate, which shows that the functional monomers in the aqueous binder give full play to the ion conduction characteristics and mechanical properties, ensure the efficient transmission of ions in the battery and fully suppress the volume expansion of the active material due to its structural damage and shedding, and effectively improve the structural stability of the electrode and the adhesion between the electrode and the current collector. In addition, the embodiments generally show a higher initial coulomb efficiency than the comparative example, which shows that the aqueous binder has advantages in improving the interface stability and electrolyte compatibility of the silicon-carbon electrode. Comparative Example 2 has poor initial coulomb efficiency due to poor interface compatibility, and Comparative Example 3 has poor capacity retention rate due to poor strength and toughness. The present invention adopts an aqueous dispersion polymerization system in combination with carboxymethyl cellulose to ensure the compatibility and stability of the binder, while achieving green environmental protection requirements and reducing environmental pollution. The binder does not contain toxic organic solvents, has a wide source of raw materials, is easy to prepare, and has significant low-cost advantages.

[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A lithium ion battery silicon-carbon negative electrode aqueous binder, characterized in that: The binder comprises a first component of carboxymethyl cellulose, a second component of a solution polymer and a third component of an emulsion polymer; Calculated by solid content, the mass ratio of the first component to the sum of the second component and the third component is 1:0.5 to 1:

5.

2. The lithium ion battery silicon-carbon negative electrode aqueous binder according to claim 1, characterized in that: Calculated by solid content, the mass ratio of the first component to the sum of the second component and the third component is 1:0.5 to 1:4; The mass ratio of the second component to the third component is 1:1 to 1:4; The solution polymer is obtained from polar monomers through solution polymerization, and the emulsion polymer is obtained from polar monomers and non-polar monomers through emulsion polymerization.

3. The lithium ion battery silicon-carbon negative electrode aqueous binder according to claim 1, characterized in that: The molecular weight M of the carboxymethyl cellulose W The molecular weight of the carbonyl group is 90,000 to 700,000, and the degree of substitution is 0.7 to 1.

2.

4. The lithium ion battery silicon-carbon negative electrode aqueous binder according to claim 1, characterized in that: The second component is prepared by the following steps: premixing a polar monomer acrylic acid with at least one of β-acryloxypropionic acid, vinyl acetate, acrylonitrile and acrylamide to obtain a premixed monomer, adding a neutralizer and then adding water to obtain a reaction solution, adding an initiator and heating in a deoxygenated environment to perform a solution polymerization reaction to obtain the second component.

5. The lithium ion battery silicon-carbon negative electrode aqueous binder according to claim 4, characterized in that: The mass proportion of acrylic acid in the premixed monomer is 40-80%; The mass concentration of the monomer in the reaction solution is 20-30%; The adding of the neutralizing agent is to neutralize 20 to 60% of the total carboxylic acid in the premixed monomers.

6. The aqueous binder for lithium-ion battery silicon-carbon negative electrode according to claim 1, characterized in that: The third component is prepared by the following steps: premixing polar monomers and non-polar monomers to obtain premixed monomers, adding an emulsifier and an appropriate amount of water to emulsify to obtain a pre-emulsion, adding an initiator to a portion of the pre-emulsion to obtain a seed pre-emulsion, heating and performing seed emulsion polymerization in a deoxygenated environment, then dripping the remaining pre-emulsion and heating again to perform a subsequent emulsion polymerization reaction to obtain the third component; The polar monomer is at least one of methacrylic acid, acrylic acid, acrylonitrile, acrylamide, β-acryloxypropionic acid and vinyl acetate; The non-polar monomers are at least two of methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate and styrene.

7. The aqueous binder for lithium-ion battery silicon-carbon negative electrode according to claim 6, characterized in that: The non-polar monomer accounts for 80-95% of the total mass of the premixed monomers; The emulsifier is one or more of SDBS, OP-10, reactive emulsifier SR-10 and reactive emulsifier DNS-86, and the added amount of the emulsifier is 4-8% of the total mass of the premixed monomers.

8. The aqueous binder for silicon-carbon negative electrode of lithium ion battery according to claim 4 or 6, characterized in that: The initiator is ammonium persulfate or potassium persulfate, and the added amount of the initiator is 0.5-1% of the total mass of the premixed monomers.

9. The method for preparing the aqueous binder for silicon-carbon negative electrode of lithium ion battery according to any one of claims 1 to 8, characterized in that The steps include: The first component, the second component and the third component are mixed in a certain mass ratio, and the pH value is adjusted to 5-9 to obtain a lithium ion battery silicon-carbon negative electrode aqueous binder.

10. Use of the aqueous binder according to any one of claims 1 to 8 in a negative electrode of a silicon-carbon lithium-ion battery.

Citation Information

Patent Citations

  • High-specific-capacity silicon-based negative electrode composite binder and preparation method for negative plate containing same

    CN106058259A

  • Preparation method of novel lithium ion battery silicon-based negative electrode binder

    CN111430712A

  • Water-based composite binder with dual-network structure, preparation method of water-based composite binder and application of water-based composite binder in lithium ion battery

    CN115832308A